(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Dovganets V. I. Analysis of the implementation results of the didactic model of the cognitive independence formation of non-linguistic specialties students studying foreign languages. The article presents the ways of realization of the didactic model of the cognitive independence formation of students of non-linguistic specialties studying foreign languages. The author analyses the implementation results of the didactic model obtained through an empirical study of the object and represents a qualitative-quantitative dynamics of students’ cognitive independence formation on the selected criteria.